Influencing Generations: Pre-service teachers' environmental worldviews at a South African university - Dianne Long (Environmental Association of Southern Africa, 2021)
One of the key means of achieving environmental mindfulness is through education. Using a social transformation orientation lens and questions in the Revised New Ecological Paradigm (NEP) scale (Dunlap, Van Liere, Mertig & Emmet Jones, 2000), this study at a South African university examines the environmental worldviews of a cohort of pre-service education students prior to and after completing an introductory module on Resources and Environmental Management as part of a Social Science course. Quantitative results indicate that the module did not change NEP scores significantly, suggesting that engagement with the course content is low and hence concern for the environment is low. The results suggest that more emphasis ought to be placed on environmental education to improve pre-service education students' mindfulness towards the environment.